Formation, characterization, and potential food application of rice bran wax oleogels: Expeller-pressed corn germ oil versus refined corn oil. (30th March 2020) - Zhao, Muxin; Lan, Yang; Cui, Leqi; Monono, Ewumbua; Rao, Jiajia; Chen, Bingcan
Graphical abstract: Highlights: Rice bran wax is a good gelator and higher concentration makes stronger oleogel. Oleogels can be formed by expeller-pressed (EP) corn germ oil. EP corn germ oil oleogels have greater yellow and red tone than refined corn oil oleogels. EP corn germ oil oleogels have weaker crystal network than refined corn oil oleogels. Both EP corn germ oil and refined corn oil oleogels have good cookie making performance. Abstract: The expeller-pressed (EP) corn germ oil oleogels were prepared using rice bran wax (RBX) at different concentrations (3, 5, 7, and 9 wt%). Their structural properties, including color, hardness, thermal behavior, rheological property, and crystal structure were evaluated. The performance of oleogels for potential food application was examined by incorporating oleogels into cookies as a fully replacement for commercial shortenings. Overall, RBX could form oleogels in both refined and EP corn germ oils at a concentration ≥3 wt%. Refined corn oil produced a stronger gel than crude corn oil. When comparing cookie characteristics, cookies made with both types of oleogels showed similar properties with commercial cookies. This result indicates that oleogels made by refined and EP corn germ oil together with RBX have the potential to imitate the functionality of commercial shortening in the baking industry.